A Dual-Construct Assessment Model of Creative Mathematical Reasoning and Critical Thinking in Primary Education: Development and Psychometric Validation - Alfaris, Renaldy; Sa’dijah, Cholis; Nusantara, Toto; Pratiwi, Nike; Arifin, Slamet (Journal of Innovation and Research in Primary Education, 2025)
Higher-order mathematical thinking encompasses both intuitive and creative cognitive processes, yet existing assessment frameworks collapse these into undifferentiated composites, limiting diagnostic precision and theoretical clarity. This study developed and validated a dual-construct assessment instrument measuring Mathematical Intuition (MI) and Creative Mathematical Reasoning (CMR) within the Number domain. Ten open-ended tasks were administered to 140 Grade 5 students selected through cluster sampling. Instrument validation involved expert review, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). Reliability was assessed using Cronbach's Alpha and Composite Reliability, while construct validity was evaluated through Average Variance Extracted and the Fornell–Larcker criterion. EFA identified two distinct factors explaining 71.2% of cumulative variance (CMR: 39.8%; MI: 31.4%), with factor loadings ranging from 0.68 to 0.86. CFA confirmed the two-factor model's superiority over a unidimensional alternative (ΔCFI = 0.08; ΔRMSEA = 0.03). Both constructs demonstrated strong reliability (α > 0.85; CR > 0.90), convergent validity (AVE > 0.50), and discriminant validity, with a moderate latent correlation (r = 0.62). The findings establish that MI and CMR are structurally separable yet functionally interdependent dimensions of mathematical cognition, consistent with dual-process theory. The validated instrument enables educators to diagnose reasoning difficulties at both the generative and elaborative phases, advancing both measurement precision and instructional targeting in primary mathematics education.